KL noir : red - Amir, Muhammad (Petaling Jaya, Malaysia : Fixi Novo, 2013)
'KL NOIR: Red is the first of 4 volumes about the Malaysian capital city's dark side. There are 14 short stories and one essay about the seedy, the sinister and sometimes the spooky. You will find murder, drug-dealing, kidnapping, sexual depravity, prostitution, celebrity secrets, suicides, academic rivalry, gangsters, police brutality, cannibalism, black magic, creepy rituals, political corruption and even busking. It's all totally fictional. Well, maybe the cannibalism is.'
Intro / Amir Muhammad -- The runner / Adib Zaini -- Mamak murder mystery / Marc de Faoite -- Asian angel / Shaz Johar -- A gift of flowers / Shih-Li Kow -- Kiss from a rose / Fadzlishah Johnanabas -- After dark, my love / Dina Zaman -- The oracle of truth / Eeleen Lee -- Chasing butterflies in the night / Kris Williamson -- The dualist / Shivani Sivaguraunathan -- Vanished / Khairulnizam Bakeri -- Cannibal vs. Ah Long / Megat Ishak -- The machete and me / Dayang Noor -- The unbeliever / Amir Hafizi -- Mud / Brian Gomez.
Keywords: Short stories, Malaysian (English); Kuala Lumpur (Malaysia) -- Fiction